Pendampingan Strategi Branding dan Digital Marketing untuk Meningkatkan Daya Jual Produk Pertanian di Desa Dander - Dela Syahwa Fitriani; Dewi Rochmayant (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
This Community Service Program (PKM) was carried out in Dander Village with the aim of increasing the marketability of agricultural products through assistance in branding strategies and digital marketing. The background of this activity stems from the low added value and limited market reach of agricultural products, most of which are still sold without clear branding and have not yet utilized digital media. The program aims to raise farmers’ awareness of the importance of brand identity, enhance their ability to design product branding, and utilize digital platforms for promotion and sales. The implementation methods included planning, socialization and branding training, digital marketing training, implementation assistance, and evaluation. Through this activity, participants were trained to create brand identities, product packaging, business social media accounts, and digital promotional content. The results showed an improvement in participants’ skills in developing branding strategies and managing digital marketing, which led to an average sales increase of 25–30%. This activity demonstrates that proper application of branding and digital marketing can enhance the competitiveness and selling value of local agricultural products in Dander Village.